Dampak Globalisasi dalam Proses Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Febria Syavanny; Silvia Anggreni BP; Ade Kurnia (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of the study was to determine the effect of globalization in the teaching and learning process, both positive and negative impacts and to determine the efforts of teachers in overcoming the negative impacts of globalization in the teaching and learning process on Pancasila and citizenship education in class XI SMKN 3 Payakumbuh. The research method uses a qualitative descriptive method. The results of the study show that the impact of globalization in the learning process of Pancasila and Civics education includes: (A) The positive impacts of globalization: 1) The increase in science and technology can enrich learning resources, 2) The values ​​and attitudes of students change in a positive direction, 3) The level of student life becomes more good, 4) The rules in learning are getting better, 5) Enriching culture in the learning process. (B) Negative impacts of globalization: 1) Students' lifestyles become consumptive and westernized, 2) Attitudes become individualistic, 4) Social inequality between students, 5) Rules or rules in the learning process, 6) Cultural fields or habits in the learning process . The conclusions of the study indicate the efforts of teachers in overcoming the negative impacts of globalization in the learning process of Pancasila and Citizenship Education, namely: (1) Overcoming the negative impacts of globalization by teachers, (2) Fostering the spirit of nationalism, (3) Practice of Pancasila values, (4) Practice of teachings religion, (5) Formation of student character. Keywords : Globalization, Pancasila Education Learning and Citizenship